Tumoral form of aspergillosis in central nervous system (cerebral aspergilloma): case report - Figueiredo, Eberval Gadelha; Fonoff, Erich; Gomes, Marcos; Macedo, Emílio; Marino Júnior, Raul (São Paulo Medical Journal, 2003)
Aspergillosis of the central nervous system is an uncommon infection, mainly occurring in immunocompromised patients. It may be presented in several forms: meningitis, mycotic aneurysms, infarcts and the tumoral form (aspergilloma). The authors report a case of a diabetic patient with cerebral aspergilloma.